Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Cabang Ambon - Pieter N. R. Rehatta; Saleh Tutupoho (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2019)
"The Effect of Job Satisfaction and Organizational Commitment on Employee Performance of the Ambon Branch of BPJS on health institutions".The purpose of this study was to determine the effect of job satisfaction and organizational commitment on the Ambon branch of BPJS on health institutions. The population in this study were employees of the Ambon branch of BPJS on health institutions. The sample in this study were 32 employees. Data collection was carried out using a questionnaire. The data analysis method used was SPSS version 16. The results of multiple regression analysis are Y = 0.280 X1 + 0.392X2. The independent variable that most influences the dependent variable is the organizational commitment variable (0.392), and the last is the job satisfaction variable (0.280). The results of the t test show that all the independent variables (job satisfaction and organizational commitment) have a significant positive effect on the dependent variable (employee performance) where all the independent variables obtain a t value greater than the t table with a sig level of less than 0.05. And the coefficient of determination (R Square) obtained is 0.323, this means that 32.3% of employee performance can be explained by job satisfaction and organizational commitment variables, while the remaining 67.7% is influenced by other variables not examined in this study.The implication of the above conclusions is that in an effort to improve employee performance, the Ambon branch of BPJS on health institutions should increase job satisfaction for employees, namely the leadership must provide more support for employees and must mutually cooperate between employees so that their sense of job satisfaction increases and increases commitment to oneself and at the company.